THE ROLE AND FUNCTIONS OF SCIENTIFIC RESEARCH METHODS IN THE STUDY OF PROFESSIONAL ETHICS AND PEDAGOGICAL CULTURE - Shavkat Norqobilovich Kazakov (Proximus Journal Publishing, 2025)
In scientific research, the appropriate selection of research methods is directly linked to the clear articulation of the research content, objectives, and tasks. The choice of methods is primarily grounded in the nature of the research object and subject—whether the phenomena under investigation are dynamic, psychological, or social in character. For instance, since processes such as pedagogical culture and professional ethics are inherently connected to human consciousness, values, inner positions, and attitudes, methods that account for subjective opinions, individual experiences, and contextual information take precedence in their study. From a scientific perspective, the methods employed in research must be inherently tied to the research's general scientific approach, methodology, and epistemological foundations. Regardless of the method chosen, it must fully correspond to the nature of the research object and serve the goals and objectives of finding a scientific solution to the problem. Scientific research is not merely a process of gathering data; it is the creation of knowledge within a specific theoretical or methodological framework. Therefore, research methods should not be viewed merely as tools for collecting information but rather as instruments that shape and construct knowledge
Keywords: knowledge; foundations; method; methodological